Yokukansan and Yokukansankachimpihange Ameliorate Aggressive Behaviors in Rats with Cholinergic Degeneration in the Nucleus Basalis of Meynert - Tabuchi, Masahiro; Mizuno, Keita; Mizoguchi, Kazushige; Hattori, Tomohisa; Kase, Yoshio (Frontiers in Pharmacology, 2017)
Yokukansan (YKS) and yokukansankachimpihange (YKSCH) are traditional Japanese Kampo medicines. The latter comprises YKS along with the medicinal herbs Citrus unshiu peel and Pinellia tuber. Both of these Kampo medicines are indicated for the treatment of night crying and irritability in children and for neurosis and insomnia in adults. In recent clinical trials, YKS exhibited ameliorative effects on the behavioral and psychological symptoms of dementia, such as aggressiveness, excitement, and irritability. In the present study, we aimed to clarify the involvement of cholinergic degeneration in the nucleus basalis of Meynert (NBM) in the development of aggressiveness in rats. Subsequently, using this animal model, the effects of YKS and YKSCH on aggressiveness were compared and the mechanisms underlying these effects were investigated. L-Glutamic acid (Glu) was injected into the right NBM of rats to induce deterioration of cholinergic neurons. On day 8 after Glu injection, aggressive behaviors were evaluated using resident–intruder tests. After the evaluation, YKS or YKSCH was administered to rats with aggressive behaviors daily for seven days. In some groups, the 5-HT1A receptor antagonist WAY-100635 was coadministered with YKS or YKSCH over the same period. In other groups, locomotor activity was measured on days 12–14 after Glu injection. On day 15, immunohistochemistry was then performed to examine choline acetyltransferase (ChAT) activities in the NBM. Aggressive behaviors had developed on day 8 after Glu injection and were maintained until day 15. YKS and YKSCH significantly ameliorated the aggressive behaviors. These suppressive effects were entirely abolished following coadministration of WAY-100635. Finally, the number of ChAT-positive cells in the right NBM was significantly reduced on day 15 after Glu injection, and treatment with YKS or YKSCH did not ameliorate these reduced cell numbers. Our results show that unilateral Glu injections into the NBM of rats leads to the development of aggressive behaviors, which is thought to reflect cholinergic degeneration. YKS and YKSCH treatments ameliorated Glu-induced aggressive behaviors, and these effects were suggested to be mediated by 5-HT1A receptor stimulation, but not by improvement of cholinergic degeneration.